Study of lighting characteristics of LED analogues of domestically produced linear fluorescent lamps - Ashryatov A. A.; Kuznetsov E. A.; Pashkov M. Yu. (Vestnik MGTU)
LED linear lamps are gaining popularity in various fields of application due to their advantages in energy efficiency, durability and lighting quality. The paper considers the designs of the tested LED lamps of domestic production by AVANLED company intended to replace fluorescent lamps T8 with a power of 18 W, and also studies their lighting characteristics. Structurally, the studied lamps are produced in two versions: with a transparent and frosted glass bulb. Analysis of the dependence of the electrical characteristics of the lamps on the network voltage (Uc) has proved that they are practically independent of changes in Uc within ± 15 %. The results of measurements of lighting characteristics have shown that most parameters correspond to the declared values: the error of color temperature does not exceed 5 %, the error of color rendering index is 0.1 %, and the pulsation index of luminous flux is within the declared 5 % and equals 0.1 %. The luminous flux at the nominal voltage of the network differs from the declared value of 1,000 lm, and the luminous flux of LED lamps with a transparent tube is less than with a matte one. The power of the lamps varies from 8 to 8.7 W, which does not correspond to the declared 9 W. The luminous efficiency of LED lamps with a color temperature of 6,500 K corresponds to the declared value. For LED lamps with a color temperature of 4,000 K (matte bulb), the luminous efficiency is 2.4 % higher than the declared value. The luminous efficiency of the remaining lamps is less than the declared value. Analysis of the spatial distribution of luminous intensity has shown that LED lamps with a frosted glass bulb are suitable for replacing fluorescent lamps in luminaires with mirror optics, and LED lamps with a transparent glass bulb are suitable for replacing fluorescent lamps in luminaires with a diffuser reducing the glare of LEDs.